2021
DOI: 10.1109/access.2021.3124017
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Downlink Multiple Users NOMA-Enable UAV-Aided Communication Systems Over Nakagami-m Fading Environments

Abstract: We evaluate a downlink non-orthogonal multiple access (NOMA)-enable UAV-aided communication system to address the demand of spectrum usage of unmanned aerial vehicles (UAVs). In this paper, multiple NOMA users are served by an UAV to improve the effective spectrum usage. Over Nakagami-m fading model, the performance of the system was investigated based on the analysis of outage probabilities (OPs) of the NOMA users, the ergodic rate, and symbol error rate of the system under two scenarios, i.e., perfect succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…One of these possible ways is to deploy diversity techniques at the BSs and/or MUs to further enhance the Pcov and ASE [30]. Additionally, the application of reconfigurable intelligent surfaces (RIS) and NOMA into the ultra-dense cellular networks is also promising [31]- [33]. The heterogeneous networks architecture where cellular networks co-exist with other networks such as cognitive radio networks, low power wide area networks (LoRa, Sig-Fox), and device-to-device communications also scales up the system spectral efficiency [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…One of these possible ways is to deploy diversity techniques at the BSs and/or MUs to further enhance the Pcov and ASE [30]. Additionally, the application of reconfigurable intelligent surfaces (RIS) and NOMA into the ultra-dense cellular networks is also promising [31]- [33]. The heterogeneous networks architecture where cellular networks co-exist with other networks such as cognitive radio networks, low power wide area networks (LoRa, Sig-Fox), and device-to-device communications also scales up the system spectral efficiency [34], [35].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that NOMA can achieve superior performance compared to the OMA when ipCSI follows a complex Gaussian distribution. In [14] [15], two unmanned aerial vehicle (UAV)-aided NOMA models were proposed. And, the outage probability, system throughput and ergodic rate performance were investigated under ipSIC assumption.…”
Section: Related Workmentioning
confidence: 99%
“…In Reference 5, the outage probability and achievable data rate of a full duplex UAV‐NOMA system with millimeter wave communication were successfully derived. On the other hand, 6 focused on calculating the outage probability for NOMA users and comparing the system's traversal rate and symbol error rate. The performance of the system was evaluated in both full SIC and incomplete SIC conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research has been conducted on UAV-NOMA systems employing multiple UAVs as base stations or utilizing UAVs as relays. 2,[5][6][7][8][9][10][11][12][13][14][15] Both References 5 and 6 adopt the Nakagami-m fading model. In Reference 5, the outage probability and achievable data rate of a full duplex UAV-NOMA system with millimeter wave communication were successfully derived.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation